Managing the implementation of planned change initiatives in the Malaysian public sector: an administrative change leadership perspective - Santokh Singh, Ajitpal Singh (2024)
Research in the field of change management has primarily focused on the private sector, resulting in a gap in the literature on the public sector context. Existing research has mainly focused on understanding the content and reasons for change, with less attention given to how change is implemented and managed in the sector. Consequently, the challenges of implementing and managing change in the public sector have not been thoroughly investigated, prompting calls for further research in this area. Similarly, there is limited literature on change leadership in the public sector, and it lacks a theoretical foundation. This study aims to bridge these gaps by examining the implementation of planned change initiatives (PCIs) in the public sector, specifically in Malaysia and the Malaysian Public Sector (MPS). The objective is to gain a comprehensive understanding of how PCIs are implemented by analysing key themes, processes, factors, and challenges that influence the change process and its leaders. Additionally, it seeks to provide insights into the roles of administrative change leaders (ACLs) and identify the necessary attributes to effectively undertake such roles. This study employed a qualitative cross-sectional methodology and was conducted from the viewpoint of ACLs. Data were collected through semi-structured interviews and focus group interviews with 28 ACLs at middle and senior levels from the Administrative and Diplomatic Service of the MPS. The data were then analysed thematically using the template analysis method, guided by a priori themes and a theoretical framework. Five central themes emerged from the analysis: envisioning change, communicating change, managing people for change, strategising change implementation, and leading change effectively. The findings indicate that PCIs are implemented in a linear and top-down manner, facilitated by top-down decision-making, communication, and leadership. They also reveal that the implementation process is significantly influenced by the sector’s contextual factors. These factors include: the prevalence of a hierarchical compliance culture, leading to passive communication and resistance manifested through non-verbal actions; the involvement of political leaders in decision-making and other aspects of change, resulting in both positive and negative impacts on the change process and ACLs; the need to manage and bridge the competing interests of various stakeholders in the change environment; and the cross-boundary nature of PCIs, requiring strategic alignment and continuous engagement for effective implementation. Consequently, the findings suggest that these factors increase the complexity of implementing and managing change in the sector, emphasising the need for thorough planning, a clear vision, and effective engagement in the change process. The findings also underscore the importance of a more participatory approach, particularly in decision-making, communication, and leadership, to address implementation gaps. Overall, this study contributes to the existing body of knowledge on change management by enhancing our understanding of how planned change is applied and managed in the public sector context. It also develops a theoretical framework for planned change implementation, providing a structured foundation for change implementation in the sector.